Review on Herbal Drugs used in Dental Care Management - Telrandhe, Umesh B.; Lokhande, Rutuja R.; Lodhe, Vishakha N.; Kosalge, Satish B.; Parihar, Shweta; Sharma, Devender (Asian Journal of Pharmaceutical Research and Development, 2021)
Nowadays teeth related disease is common among all ages of people and children. Ten out of five children are suffering from tooth decay due to the consumption of more sweets, chocolates, and eatable items by children. Various eatables affect the teeth and decay the teeth rapidly, so we need to understand the phenomena of diseases which is responsible for infection in teeth. Main objective of this review project is to collect the information and role of various herbal drugs used in Dental Care and for its management. Also represent systematic plant profile which not only useful in treatment of the teeth but also give the phytochemicals and therapeutic information of plants used the in management of teeth diseases.